Influence of the endothelial glycocalyx on cerebral blood flow in mice - Vogel, Johannes; Sperandio, Markus; Pries, Axel Radlach; Linderkamp, Otwin; Gaehtgens, P.; Kuschinsky, Wolfgang (Journal of cerebral blood flow & metabolism, 2000)
The endothelial surface layer (glycocalyx) of cerebral capillaries may increase resistance to blood flow. This hypothesis was investigated in mice by intravenous administration of heparinase (2500 IU/kg body weight in saline), which cleaves proteoglycan junctions of the glycocalyx. Morphology was investigated by transmission electron microscopy. Cerebral perfusion velocity was recorded before and during heparinase or saline treatment using laser-Doppler flowmetry. In addition, cerebral blood flow (CBF) was measured 10 minutes after heparinase or saline treatment using the iodo[14C]antipyrine method. Laser-Doppler flowmetry and CBF measurements were performed during normocapnia and severe hypercapnia (Pco2: 120 mm Hg). After heparinase, morphology showed a reduced thickness of the glycocalyx in cortical microvessels by 43% (P < 0.05) compared with saline-treated controls. Under normocapnic conditions, a 15% (P < 0.05) transient increase of cerebral flow velocity occurred 2.5 to 5 minutes after heparinase injection. Laser-Doppler flow and CBF returned to control values ten minutes after the injection. However, during severe hypercapnia, heparinase treatment resulted in a persisting increase in laser-Doppler flow (6%, P < 0.05) and CBF (30%, P < 0.05). These observations indicate the existence of a flow resistance in cerebral capillaries exerted by the glycocalyx. The transient nature of the CBF increase during normocapnia may be explained by a vascular compensation that is exhausted during severe hypercapnia.